Geothermal Pipeline - Geo-Heat Center (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1988)
The workshop will address the scientific and technical aspects of solids deposition in geothermal systems, including the reservoir, wellbore, pipelines, equipment, direct use and electric power plants. The workshop will be held at the University of Iceland in Reykjavik. Field trips will be arranged to local geothermal fields and power plants, both during and after the workshop: an afternoon trip during the workshop and a one-day trip the last day. The registration fee will be set to cover direct expenses. There are no funds available to aid participants